PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK TWO STAY TWO STRAY UNTUK MENGATASI KESALAHAN SISWA MENYELESAIKAN SOAL CERITASUBPOKOK BAHASAN LUAS PERMUKAAN DAN VOLUME BALOK KELAS VIII B SEMESTER GENAP SMP NEGERI 7 JEMBER TAHUN PELAJARAN 2012/2013 - Khasanah, Retno Nur; Trapsilasiwi, Dinawati; Kristiana, Arika Indah (Department of Mathematics Education , University of Jember, 2014)
Abstract. The research aims to know the application of Two Stay Two Stray teaching for decrease student’s mistakes for surface area and volume of the beam topic at eight grade of junior high school. Two Stay Two Stray teaching provide an opportunity for groups to share results and information with other groups. The subject of research is students of VIII B class SMPN 7Jember in even semester academic year 2012/ 2013. The kinds of student’s mistakes consist of error using data, error of theorem or definition, technical errors, and another mistakes. This research design is Classroom Action Research (CAR) and the method of data collecting using observation, interview, test and documentation. The result of research indicate that the result of learning activity increase of student’s activity in cycle I reach 73,06% whereas in cycle II reach 85,39% . While the student’s mistakes at cycle I reach 71.88% and cycle II 17,43%. So, the mode of teaching can increase student’s activity and decrease the student’s mistakes. Key Words : Two Stay Two Stray teaching, survace area and volume, beam, student’s activity, student’s mistakes